Cardio-Oncology: An Update on Cardiotoxicity of Cancer-Related Treatment. Issue 6 (18th March 2016) - Lenneman, Carrie G.; Sawyer, Douglas B.
Abstract : Through the success of basic and disease-specific research, cancer survivors are one of the largest growing subsets of individuals accessing the healthcare system. Interestingly, cardiovascular disease is the second leading cause of morbidity and mortality in cancer survivors after recurrent malignancy. This recognition has helped stimulate a collaboration between oncology and cardiology practitioners and researchers, and the portmanteau cardio-oncology (also known as onco-cardiology) can now be found in many medical centers. This collaboration promises new insights into how cancer therapies impact cardiovascular homeostasis and long-term effects on cancer survivors. In this review, we will discuss the most recent views on the cardiotoxicity related to various classes of chemotherapy agents and radiation. We will also discuss broadly the current strategies for treating and preventing cardiovascular effects of cancer therapy.